2017
DOI: 10.1111/exd.13408
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids: The mode of action in bullous pemphigoid

Abstract: Bullous pemphigoid (BP) is the most common of pemphigoid diseases caused by autoantibodies against the structures of dermoepidermal junction followed by complement activation, innate immune cell infiltration, neutrophil proteinase secretion and subepidermal blister formation. The first-line treatment of BP is topical and systemic glucocorticoids (GC). Regulation of the immune system and inflammatory cells is the main target of GC actions. GCs act through genomic and non-genomic mechanisms.The human glucocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 116 publications
(175 reference statements)
0
5
0
1
Order By: Relevance
“…Bullous pemphigoid (BP) is a skin-specific autoimmune disease characterized by subepidermal blisters (14). Systemic glucocorticoids and immunosuppressive agents are effective treatment options for BP (5, 6), but they increase the risk of lethal infections, particularly in elderly patients (7, 8). The autoimmune mechanisms involved in BP have been well-discussed based on clinical and experiential evidence (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Bullous pemphigoid (BP) is a skin-specific autoimmune disease characterized by subepidermal blisters (14). Systemic glucocorticoids and immunosuppressive agents are effective treatment options for BP (5, 6), but they increase the risk of lethal infections, particularly in elderly patients (7, 8). The autoimmune mechanisms involved in BP have been well-discussed based on clinical and experiential evidence (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we detected Th17 cell responses against BP180 in a few patients with BP and only to a minor extent in EP with pruritic disorders. The role of IL-17-producing T cells in BP has been partially elucidated (30,(42)(43)(44)(45)(46). Recently, it was shown that mRNA levels of IL-17 were upregulated in perilesional skin of BP patients (30,46) and inhibition of IL-17 with anti-IL-17 antibodies prevents BP180 IgG-induced blister formation (30,46).…”
Section: Discussionmentioning
confidence: 99%
“…23,43 However, the refractory nature of some patients to corticosteroids merits further study. 44,45…”
Section: Bullous Pemphigoidmentioning
confidence: 99%